Sistemas nanoestruturados condutores baseados em nanocompósitos poliméricos condutores e mantas eletrofiadas condutoras - Silva, Aline Bruna da (Universidade Federal de São Carlos, 2013)
In this work its was investigated the influence of the processing on the electrical and dielectric properties of nanostructured polymeric systems obtained by differents techniques. The morphology and structure of the materials were correlated to their percolation threshold by applying the percolation theory. The systems studied were: i) conductive blends of poly(vinylidene fluoride) (PVDF) with polypyrrole (PPy), PVDF/ multiwall carbon nanotube (MWCNT) composites and PVDF/PPy/MWCNT hybrid systems, produced by melt mixing; ii) PVDF/ copper nanowires (CuNW) and MWCNT/PVDF nanocomposites produced by miscible solvent mixing and precipitation methods (MSMP); iii) nanofibers of nanocomposites of PA6/MWCNT, PVDF/MWCNT and PVDF/CuNW and from blends of PA6/ poly(aniline) (PAni) doped with p-toluene sulfonic acid (TSA), by electrospinning. For the systems produced by melt mixing the percolation thresholds were 10 and 0.3 wt %, for PVDF/PPy and PVDF/MWCNT, respectively, while the hybrid systems showed lower percolation thresholds and much higher electrical conductivities at all concentrations than the binary systems. For the systems produced by MSMP method the percolation thresholds were 0.13 and 0.29 v%, for the MWCNT/PVDF and CuNW/PVDF nanocomposites, respectively. It was observed also that the CuNW/PVDF nanocomposites had the highest real permittivity combined with a low dissipation factor (tan ). The non woven mats obtained by electrospinning presented insulating behavior. However, to take advantage of the high surface area and porosity of the mats the surface of the nanofibers were recovered with MWCNT by dipping the mats in an aqueous solution with MWCNT. A strong interaction between the MWNTs and the nanofibers was observed: even after ultrasonication, the adsorbed MWCNT remained attached to the surface of the nanofibers´ mats. After the treatment the mats displayed conductivities between 10-5 and 10-2 S/m.
Nanostructured polymeric systems based on conductive nanocomposites and conductive electrospun mats
Keywords: Polímeros; Nanocompósitos; Condutividade elétrica; Eletrofiação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA